The Content And Methodological Features Of An Integrated Approach To The Formation Of Professional Competencies In Students - Ismoilov Elmurod Olloberdi o‘g‘li (Genius Publishing Group, 2022)
This article presents the results of research on the use of the integration of mathematics with general and specialized disciplines in the development of professional competence of students. In addition, the article explains in detail the relationship of mathematics to the general and special sciences through diagrams. As a result of the analysis, a structural-functional model of developing students' professional competence was developed
Keywords: Integration; Integration Of Sciences; Practical Assignment; Professional Competence